The impact of parental employment and unemployment on children and young people - Cusworth, Linda (2007)
Over recent decades there have been dramatic changes in the employment patterns of men and women, with particularly significant increases in employment rates among mothers. Government policy has also increasingly given attention to encouraging parents, particularly lone mothers, into work, with a focus on paid work as a defence against poverty. These trends and policy changes affect the everyday lives of both parents and children, and give rise to questions about the potential impact that parental employment patterns have on children and young people.